Assessment Of Cost‐Effective Alternatives For Improving Irrigation Systems In The Nile Delta†. (8th September 2015) - Abou El‐Hassan, W.H.; El‐Kassar, G.; Fujimaki, H.; Kitamura, Y.; Khater, A.
Abstract Preliminary studies were conducted to test new design criteria incorporated in the Sefsafa Canal (SC) with the aim of reducing water application costs without sacrificing irrigation performance. For comparison, we also studied the Meet‐Yazied Canal (MYC) (which is run without the new techniques). The cost‐reduction measures used in this study included reduction of pump discharge rates and the use of electricity instead of diesel. We found that the location of farms along the irrigation canal had little effect on pump operation hours and amount of applied water; instead, crop patterns were the most important factor in this regard. The water use index (WUI), which is the ratio of applied water to required water, was higher in the SC than in the MYC and El‐Mesk Canal (MC). Decreasing the pump discharge increased the amount of applied water to meet crop water requirements. During the winter, the WUI values of 1.11–1.16 achieved discharge rates of 70–80 l s−1 and were considered the optimal values of WUI. Further studies are required to avoid excessive application of water during the summer. The application of new techniques prompted farmers to irrigate their fields at night, thereby reducing water losses and installation and operational costs, and promoting equitable water distribution along the entire irrigation canal and throughout the command area. Copyright © 2015 John Wiley & Sons, Ltd.